2020
DOI: 10.1007/s00421-020-04491-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute aerobic, resistance and combined exercises on 24-h glucose variability and skeletal muscle signalling responses in type 1 diabetics

Abstract: Purpose To compare the effect of high-intensity aerobic (AER), resistance (RES), and combined (COMB: RES + AER) exercise, on interstitial glucose (IG) variability and skeletal muscle signalling pathways in type 1 diabetes (T1D). Methods T1D participants (6 M/6F) wore a flash glucose monitoring system in four randomized sessions: one control (CONT), and one AER, RES and COMB (40 min each). Mean amplitude of glycemic excursions (MAGE), standard deviation (SD) and coefficient variation (CV) of IG were used to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 40 publications
3
24
0
1
Order By: Relevance
“…The present study, however, demonstrated that exercise increased the glucose fluctuation indices compared with the control trial. Of note, in the present study, the meal size was increased in the exercise trials to achieve an individual energy balance over 24 h, while in the previous studies, the same meals were provided during trials with or without an exercise session (Li et al, 2018; Minnock et al, 2020; Praet et al, 2006; Rees et al, 2019; Terada et al, 2016). It is possible that the difference in the energy balance or meal size plays a role in controlling glucose fluctuation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The present study, however, demonstrated that exercise increased the glucose fluctuation indices compared with the control trial. Of note, in the present study, the meal size was increased in the exercise trials to achieve an individual energy balance over 24 h, while in the previous studies, the same meals were provided during trials with or without an exercise session (Li et al, 2018; Minnock et al, 2020; Praet et al, 2006; Rees et al, 2019; Terada et al, 2016). It is possible that the difference in the energy balance or meal size plays a role in controlling glucose fluctuation.…”
Section: Discussionmentioning
confidence: 81%
“…The same exercises performed 80 min after breakfast, however, do not affect MAGE. In addition, MAGE is decreased by 2 sets of 6 resistance exercises (at 80% of 1‐repetition maximum) and combined exercise (20 min each of aerobic exercise at 80% of heart rate reserve and 1 set of 6 resistance exercises) for 40 min performed in a fasting condition, but is not affected by aerobic exercise for 40 min (Minnock et al, 2020). Although the results of the previous studies were inconsistent, if the exercise had any effect on the glucose fluctuation, the glucose fluctuation indices were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…21 In summary, both endurance and resistance exercise mitigate skeletal muscle insulin resistance. 88 Combining aerobic and resistance exercise might offer superior effects on glucose homeostasis compared to aerobic or resistance exercise alone, [89][90][91] as each type of exercise regulates some glucose-uptake genes that are not regulated by the other. Our analysis provides a molecular framework for how these two types of exercise elicit improvements in glucose homeostasis as they seemingly engage distinct pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patients, elevation of glycolytic enzymes including ENO1 is used as a biomarker for endogenous renoprotective factors (Gordin et al, 2019). Aerobic exercise combined with resistance exercise is able to enhance the activation of EEF2, contributing to improved glycemic control and maintenance of muscle health in type 1 diabetes (Minnock et al, 2020). ERPS can also be the potential biomarker to distinguish the type 2 diabetes and healthy person (Chu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%